A distributed admission control model for class-based networks using edge-toedge QoS and SLS monitoring - Lima, Solange (2002)
The advent of class-based networks has brought new needs for network traffic control in order to assure a certain QoS level. Despite the existing proposals, achieving a generic admission control (AC) strategy for traffic entering these networks is still an open issue. This paper provides new insights on how AC shall be accomplished proposing an encompassing AC model for multi-service class-based networks, which covers both intra-domain and end-to-end operation, without requiring changes in the network core and complex AC signaling. For each service type, AC is distributed and based on both on-line edge-to-edge monitoring of relevant QoS parameters and SLSs utilization. Service monitoring, performed at egress nodes, provides adequate metrics to ingress nodes which take implicit or explicit AC decisions based on service-dependent criteria. Although being oriented to flow AC, the model can easily be applied to SLS AC. SLS auditing and SLS traffic conditioning are tasks also covered.